CCNA2 facilitates epithelial-to-mesenchymal transition via the integrin αvβ3 signaling in NSCLC - Ruan, Jun Shan (Int J Clin Exp Pathol, 2017)
Non-small cell lung carcinoma (NSCLC) is the most common malignancy with the highest morbidity and mortality. Studies have demonstrated that the abnormal expression of cyclin-A2 (CCNA2) is associated with multiple malignancies, yet its functional role in NSCLC metastasis remains to be elucidated. In the present study, we investigated the role of CCNA2 in regulating migration and invasion of NSCLC cells by establishing NSCLC cell strains with constitutively silenced or elevated CCNA2 expression. We demonstrated that ectopic expression of CCNA2 accelerates NSCLC cells migration and invasion in vitro through cell wound scratching and Transwell invasion assays. Conversely, further analysis indicated that suppression of CCNA2 expression via siRNA inhibits metastasis of NSCLC cells. In addition, we studied the correlation between CCNA2 expression and overall survival using the Kaplan-Meier Plotter database in NSCLC cancers. There was correlation between CCNA2 expression levels and patient survival. Finally, our findings demonstrate that CCNA2 promotes invasion and migration of NSCLC cells through integrin αVβ3 signaling pathway. Collectively, this study provides novel insights into that CCNA2 represents a crucial regulator of NSCLC cells metastasis and suggests targeted treatment of CCNA2-expressing cancer serves as a new therapeutic target for NSCLC.